Analysis of Heat Rate Co-firing Pacitan PLTU - Kiki Darmawan; Luchyto Chadra Permadi; Bella Cornelia Tjiptady; Ratna Fajarwati Meditama; Indah Martha Fitriani; Faisol Khoufi Asshidiqi (Universitas Islam Raden Rahmat, Malang, 2025)
Through RUEN in 2025, the government is launching a co-firing program for coal-fired power plants towards achieving net zero emissions. Biomass is one solution to replace or replace fossil fuels in the field of energy supply. Some of the energy plants commonly used for co-firing are calliandra and gamal. The aim of this research is to analyze the Heat Rate efficiency of the use of calliandra and gamal biomass. This research method in quantitative form to achieve measurable results. The results of the analysis of using calliandra biomass at a percentage of 5% produce an NHPR of 2975 kCal/kWh. This value is greater than the use of gamal biomass at a percentage of 5% with a GHPR of 2942 kCal/kWh, and using a percentage of 10% produces an NHPR of 2986 kCal/kWh and at 10% gamal co-firing it produces an NHPR of 2920 kCal/kWh, the smallest thermal efficiency value is produced when the plant uses 10% kalindran co-firing with a value of 30.9%. and the highest thermal efficiency of the generator is when 10% galvanic co-firing is used.